Code-Switching in Lecturer-Students’ Interaction in Thesis Examination - Siti Rahmani; Iskandar Abdul Somad; Nira Erdiana (English Education Journal, 2022)
Choosing a code when interacting is one of the opportunities that a bilingual has. Code-switching is usually used by bilinguals when interacting with the other person. This study tries to find the types of code-switching and the categories of reasons for using code-switching in lecturer- students’ interactions in thesis exams. This research used a qualitative method with a case study approach. The data was in the form of utterances obtained from recorded interactions of five thesis examination sessions in the English undergraduate program at Syiah Kuala University. The data was analyzed through several processes, including transcribing, data condensation, identifying, marking, grouping, displaying data, and making inferences. The data was analyzed using the theory proposed by Stockwell and Hoffman. From the analysis, it was found that there are three types of code-switching, namely tag switching, inter-sentential, and intra-sentential. Related to the categories of reasons for using code-switching, the researcher found 5 from 7 reasons to do code-switching in lecturer-students’ interaction in thesis examination. The researcher hoped that the next researcher will further analyze the code-switching that occurs in the thesis exam, not only analyzing the types of code-switching and the reasons for using code-switching, but also analyzing the other side of linguistics.